EFFECTS OF SUBSTRATES ENRICHED WITH ORGANIC MATTER ON GROWTH PARAMETERS OF WHITE BOLAINA (Guazuma crinita C. Martius) IN NURSERY-PUERTO INCA - RODRIGUEZ-ORTEGA, Gerson (2023)
Deforestation globally and in Peru is a continuous problem, and actions must be taken to mitigate that activity, with the aim of recovering the services provided by the ecosystems through reforestation with quality seedlings of suitable species, generating artificial forests. The objective of this research was to determine the effect of substrates enriched with organic fertilizers on growth parameters of bolaina blanca seedlings in the nursery-garden. The treatments were made of a basic substrate (agricultural soil + sand) enriched with cattle manure (T1), chicken manure (T2), island guano (T3) and decomposed sawdust (T4) and were compared with a Control (T0), in Puerto Inca-Huánuco. A complete randomized design was established with 5 treatments and 3 repetitions, evaluating plant height, stem diameter and number of leaves. The results obtained indicate that at 45 days after ringing (DDR) treatments T3, T4 and T2 respectively, reached the highest number of leaves. At 75 DDR, treatments T4 and T3 achieved the highest plant height and largest diameter; denoting a precocious behavior due to the effect of the organic sources used to achieve the quality attributes required for the respective plantation.